Human capital and the level and quality of life in the European Union countries in the period 2005-2015 - Madrak-Grochowska, Małgorzata (Kapitał ludzki oraz poziom i jakość życia w krajach Unii Europejskiej w latach 2005-2015, 2019)
The major research objective of this article is to investigate the connections between human capital accumulated in 25 EU countries and the level and quality of life recorded in these countries in the 2005-2015 time period. Three research tasks were subordinated to the process of reaching the defined goal, the first of which was to make a concise theoretical presentation of the concept and determinants of human capital in the broad sense. The second stage of the research conducted involved the construction (using taxonomic methods) of a synthetic measure of human capital accumulated in the EU in 2005-2015 and the development of international rankings for the degree of human capital development. The final task is the most important one considering the objective of the work – this was the analysis of correlation relationships occurring in 2005-2015 between the synthetic measure of human capital and selected indicators of the level and quality of life estimated for the EU countries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 61-76